Visual Eisegesis on Newly Created Ghanaian Cultural Symbols with Inspirations from Existing Adinkra Symbols in Ghana - Michael Ato Essuman; Dickson Adom; Isaac Asare-Aboagye; Kwame Baah Owusu Panin (Indigenous: Jurnal Ilmiah Psikologi, 2024)
In Ghanaian culture, our predecessors' perception of symbols and meanings hold profound significance, reflecting the rich cultural traditions and beliefs embedded in the society's heritage. The perception of symbols in Ghana's cultural traditions depicts the visual language communicating history, values, and identity. Symbols in Ghana are generally perceived to be merely decorative and not recognized as carriers of deep meanings, handed down through generations, encapsulating stories, proverbs, and spiritual beliefs. There is a need for indigenous communities to be involved in the creation and interpretation of cultural symbols, especially those inspired by Adinkra symbols in Ghana. This study aims to describe the meaning of symbols rooted in Ghana's rich cultural traditions by creating designs and meanings based on inspirations from Adinkra symbols. The study employed phenomenology and creative arts-based research methods under the qualitative research design. Personal interviews and focus group discussions were used in data collection, and participants were purposively sampled based on their experiences with the newly created Ghanaian cultural symbols. The study results showed the perceptual gap between the actual meanings of the symbols and what the respondents meant by interpreting these symbols through the lens of their cultural upbringing, historical knowledge, societal values and the new symbols as a continuation of Ghana's rich cultural heritage, bridging the past with the present.